2021
DOI: 10.1093/sleep/zsab064
|View full text |Cite
|
Sign up to set email alerts
|

Risk of in-hospital falls among medications commonly used for insomnia in hospitalized patients

Abstract: Study Objectives To investigate the risk of in-hospital falls among patients receiving medications commonly used for insomnia in the hospital setting. Methods Retrospective cohort study of all adult hospitalizations to a large academic medical center from 1/2007 to 7/2013. We excluded patients admitted for a primary psychiatric disorder. Medication exposures of interest, defined by pharmacy charges, included benzodiazepines, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 40 publications
1
3
0
Order By: Relevance
“…In fact, having elimination issues have resulted as fall predictor in other studies before [7,24]. Among studied medications, the use of hypnotics and opioids resulted as independent fall predictors in line with ndings reported from previous authors [3,[8][9][10][28][29][30]. Both these two medication categories have effects on patient's cognitive status by in uencing their space and time orientation and motor capabilities, which may explain this nding [7][8][9]11].…”
Section: Discussionsupporting
confidence: 80%
“…In fact, having elimination issues have resulted as fall predictor in other studies before [7,24]. Among studied medications, the use of hypnotics and opioids resulted as independent fall predictors in line with ndings reported from previous authors [3,[8][9][10][28][29][30]. Both these two medication categories have effects on patient's cognitive status by in uencing their space and time orientation and motor capabilities, which may explain this nding [7][8][9]11].…”
Section: Discussionsupporting
confidence: 80%
“…8,9 Unfortunately, epidemiologic studies have also revealed that older adults who chronically take prescription hypnotics to help their sleep also have higher levels of incident dementia 7,10,11 as well as higher mortality, 7,12 although the direction of causality is not known. Prescription hypnotics have also been associated with greater nighttime fall risk 13 and greater risk of hip fracture 14 in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…24 These medications are also known to be associated with various side effects, including delirium, orthostatic hypotension, dizziness, motor impairment such as muscle weakness and extrapyramidal symptoms, and visual impairment, 25 and were significantly associated with falls in this study; this finding was similar to those of previous studies. 6,10 However, unlike BZs and Z-drugs, the new hypnotic medications, lemborexant, suvorexant, and ramelteon, do not interact with GABA receptors. 24 Ramelteon utilizes melatonin, which controls circadian rhythms through G protein-coupled receptors (MT1/MT2) and lemborexant and suvorexant utilize orexin antagonists through orexin receptors to regulate sleep cycles.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Hypnotic medications are recognized risk factors for falls, 4 and their use often increases during hospitalization because of changes in both the environment and the patient's condition, leading to insomnia. 5 While benzodiazepine hypnotics (BZs) have been previously reported to be associated with falls, 6 in recent years, new hypnotic medications, such as lemborexant, suvorexant, and ramelteon, have become available. However, there is a dearth of multicenter studies examining the association between these novel hypnotic medications and falls.…”
Section: Introductionmentioning
confidence: 99%